Sea-Level Change along the Emilia-Romagna Coast from Tide Gauge and Satellite Altimetry - Matteo Meli; Marco Olivieri; Claudia Romagnoli (Remote Sensing, 2020)
Coastal flooding and retreat are markedly enhanced by sea-level rise. Thus, it is crucial to determine the sea-level variation at the local scale to support coastal hazard assessment and related management policies. In this work we focus on sea-level change along the Emilia-Romagna coast, a highly urbanized, 130 km-long belt facing the northern Adriatic Sea, by analyzing data from three tide gauges (with data records in the last 25–10 years) and related closest grid points from CMEMS monthly gridded satellite altimetry. The results reveal that the rate of sea-level rise observed by altimetry is coherent along the coast (2.8 ± 0.5 mm/year) for the period 1993–2019 and that a negative acceleration of −0.3 ± 0.1 mm/year is present, in contrast with the global scale. Rates resulting from tide gauge time series analysis diverge from these values mainly as a consequence of a large and heterogeneous rate of subsidence in the region. Over the common timespan, altimetry and tide gauge data show very high correlation, although their comparison suffers from the short overlapping period between the two data sets. Nevertheless, their combined use allows assessment of the recent (last 25 years) sea-level change along the Emilia-Romagna coast and to discuss the role of different interacting processes in the determination of the local sea level.